Fireproof - Kendrick, Alex, 1970-; Kendrick, Stephen, 1973-; Cameron, Kirk, 1970-; Bethea, Erin, 1982-; Bevel, Ken.; Dervan, Stephen; Young, Eric.; McLeod, Jason; Malcolm, Harris; Malcom, Phyllis; Revell, Perry; Makulinski, Stephanie; et al. (Culver City, Calif. : Sony Pictures Home Entertainment, 2009)
Lt. Caleb Holt lives by the old firefighter's adage: Never leave your partner behind - it's a natural instinct. But when it comes to marriage, it's another story. After a decade of marriage, Caleb and Catherine have drifted so far apart that they are ready to move on without each other. As the two prepare for divorce, Caleb's dad asks his son to try The Love Dare experiment. While hoping the experiment has nothing to do with his parents' newfound faith, Caleb commits to the challenge. Now he will have to attempt to love his wife while avoiding God's love for him. He will need to be able to demonstrate love over and over again to a person who is no longer receptive to his love.
DVD, anamorphic widescreen (1.85:1); Dolby Digital.
English, dubbed Spanish dialogue; optional Chinese, English, French, Portuguese or Spanish subtitles; closed-captioned.
Kirk Cameron, Erin Bethea, Ken Bevel, Stephen Dervan, Eric Young, Jason McLeod, Harris Malcolm, Phyllis Malcom, Perry Revell, Stephanie Makulinski, Renata Williams, Dwan Williams, Amberly Marquard.
Director of photography, Bob Scott ; editor, Bill Ebel, Alex Kendrick ; music composed by Mark Willard ; costume designer, Terri Catt ; production designer, Sheila McBride.
MPAA rating: PG; for thematic material and some peril.
Special features: Filmmakers' commentary; deleted scenes; Firegoofs, jokes and pranks; Fireproof resources; "Fireproof: behind the scenes" featurette; "Marriage matters" featurette; Wayne on Wayne interview; Fireproof in 60 seconds; Love dare promo.
Keywords: Fire fighters -- United States -- Drama; Divorce therapy -- United States -- Drama; Fathers and sons -- United States -- Drama; Intimacy (Psychology) -- Drama; Religious films; Melodrama; Video recordings for the hearing impaired; Feature films; Fiction films; Religious -- Feature; Melodrama -- Feature